Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve for [tex]\( (p \circ q)(x) \)[/tex]:
First, we need to understand what [tex]\( (p \circ q)(x) \)[/tex] means. It represents the composition of the two functions [tex]\( p(x) \)[/tex] and [tex]\( q(x) \)[/tex], so we substitute [tex]\( q(x) \)[/tex] into [tex]\( p(x) \)[/tex].
Given the functions:
[tex]\[ p(x) = 2x^2 - 4x \][/tex]
[tex]\[ q(x) = x - 3 \][/tex]
The composition [tex]\( (p \circ q)(x) \)[/tex] is defined as [tex]\( p(q(x)) \)[/tex]. So, we substitute [tex]\( q(x) \)[/tex] into [tex]\( p(x) \)[/tex]:
1. Substitute [tex]\( q(x) = x - 3 \)[/tex] into [tex]\( p(x) \)[/tex]:
[tex]\[ p(q(x)) = p(x-3) \][/tex]
2. Now, replace [tex]\( x \)[/tex] in [tex]\( p(x) \)[/tex] with [tex]\( x-3 \)[/tex]:
[tex]\[ p(x-3) = 2(x-3)^2 - 4(x-3) \][/tex]
3. Simplify the expression:
[tex]\[ (x-3)^2 = x^2 - 6x + 9 \][/tex]
So,
[tex]\[ 2(x-3)^2 = 2(x^2 - 6x + 9) = 2x^2 - 12x + 18 \][/tex]
And,
[tex]\[ -4(x-3) = -4x + 12 \][/tex]
4. Combine these results:
[tex]\[ p(x-3) = 2x^2 - 12x + 18 - 4x + 12 \][/tex]
Simplifying further,
[tex]\[ p(x-3) = 2x^2 - 16x + 30 \][/tex]
Thus, [tex]\( (p \circ q)(x) = 2x^2 - 16x + 30 \)[/tex].
Therefore, the correct answer is:
[tex]\[ 2 x^2 - 16 x + 30 \][/tex]
So, the correct option is:
[tex]\[ 2 x^2 - 16 x + 30 \][/tex]
First, we need to understand what [tex]\( (p \circ q)(x) \)[/tex] means. It represents the composition of the two functions [tex]\( p(x) \)[/tex] and [tex]\( q(x) \)[/tex], so we substitute [tex]\( q(x) \)[/tex] into [tex]\( p(x) \)[/tex].
Given the functions:
[tex]\[ p(x) = 2x^2 - 4x \][/tex]
[tex]\[ q(x) = x - 3 \][/tex]
The composition [tex]\( (p \circ q)(x) \)[/tex] is defined as [tex]\( p(q(x)) \)[/tex]. So, we substitute [tex]\( q(x) \)[/tex] into [tex]\( p(x) \)[/tex]:
1. Substitute [tex]\( q(x) = x - 3 \)[/tex] into [tex]\( p(x) \)[/tex]:
[tex]\[ p(q(x)) = p(x-3) \][/tex]
2. Now, replace [tex]\( x \)[/tex] in [tex]\( p(x) \)[/tex] with [tex]\( x-3 \)[/tex]:
[tex]\[ p(x-3) = 2(x-3)^2 - 4(x-3) \][/tex]
3. Simplify the expression:
[tex]\[ (x-3)^2 = x^2 - 6x + 9 \][/tex]
So,
[tex]\[ 2(x-3)^2 = 2(x^2 - 6x + 9) = 2x^2 - 12x + 18 \][/tex]
And,
[tex]\[ -4(x-3) = -4x + 12 \][/tex]
4. Combine these results:
[tex]\[ p(x-3) = 2x^2 - 12x + 18 - 4x + 12 \][/tex]
Simplifying further,
[tex]\[ p(x-3) = 2x^2 - 16x + 30 \][/tex]
Thus, [tex]\( (p \circ q)(x) = 2x^2 - 16x + 30 \)[/tex].
Therefore, the correct answer is:
[tex]\[ 2 x^2 - 16 x + 30 \][/tex]
So, the correct option is:
[tex]\[ 2 x^2 - 16 x + 30 \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.